Ultrasound-Guided Lumbar Transforaminal Epidural Injections; A Single Center Fluoroscopic Validation Study - Masoud Hashemi; Payman Dadkhah; Mehrdad Taheri; Seyed Mohammdareza Haji; Seyed Abootorabi; Bahram Naderi-nabi (Bulletin of Emergency and Trauma, 2019)
Objective: To investigate the success rate (technical precision) of ultrasound-guided lumbar transforaminal epidural steroid injection, which was validated by conventional fluoroscopic technique.Methods: A total of 20 patients with unilateral single-level lumbar foraminal disc protrusion causing radiculopathy were enrolled. Using transforming route, the needle location was determined by an axial (transvers) view of the ultrasound with fluoroscopic confirmation. We determined the needle placement accuracy of ultrasound- guided lumbar transforaminal injections approach. Results: The accuracy of ultrasound-guided interventions was 90% as confirmed by fluoroscopy. There were 2 failed cases at the L4-L5 level in the US-guided. The success rate in L5-S1 level was 100%, in L4-L5 level was 80% and in L3-L4 level was 100%. No complications were noted.Conclusion: Ultrasound-guided lumbar transforaminal epidural injections are accurate and feasible in clinical setting with an accuracy of 90% and no complications.